Outer Children Marriages Status After Constitutional Court Decision No: 46/PUU-VII/2010 - Sri Budi Purwaningsih (Rechtsidee, 2014)
The decision of the Constitutional Court of the Republic of Indonesia No.46/PUU-VIII / 2010 dated 17 February 2012, granted the judicial review of Article 43 (1) of Law No. 1 of 1974 on Marriage by deciding that the article should read "Children who are born outside of marriage just had a civil relationship with her mother and her mother's family as well as with men as a father who can be proved based on science and technology and / or evidence, has blood ties according to law, including a civil relationship with his father's family". This Indonesian Constitutional Court's decision bring Juridical consequence that illegitimate children not only have a legal relationship with her mother, but also has a legal relationship with the father (biological) and his father's family, as long as it is proven with science and technology. The Constitutional Court's decision is a starting point in the legal protection of illegitimate children, namely the "right alignment" between the illegitimate child with the legitimate son. Illegitimate children have the rights to demand their civil rights toward their father (biological) as the same rights obtained by the legitimate son. How To Cite: Purwaningsih, S. (2014). Outer Children Marriages Status After Constitutional Court Decision No: 46/PUU-VII/2010. Rechtsidee, 1(1), 119-130. doi:http://dx.doi.org/10.21070/jihr.v1i1.99